Social Service Providing Basic Food Assistance As A Form Of Higher Education Service To The Community At The Said Muhammad Abu Bakar Al-Jupri Batam Foundation And The Al-Jufri Orphanage Orphanage - Haufi Sukmamedian; Andri Wibowo; Yudha Wardani; Tirta Mulyadi; Dailami; Wahyudi Ilham; Agung Edy Wibowo; M. Sani Al Fikri (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
Community Service Activities (PKM) with the title